The emissions gap report 2017: a UN environment synthesis report (UNEP2, 2017)
"The goal of the Paris Agreement on climate change, as agreed at the Conference of the Parties in 2015, is to keep global temperature rise this century to well below 2 degrees Celsius above pre-industrial levels. It also calls for efforts to limit the temperature increase even further to 1.5 degrees Celsius. The UN Environment Emissions Gap Report 2017 presents an assessment of current national mitigation efforts and the ambitions countries have presented in their Nationally Determined Contributions, which form the foundation of the Paris Agreement. The report has been prepared by an international team of leading scientists, assessing all available information."